Biomineralization process in hard tissues: The interaction complexity within protein and inorganic counterparts. (15th January 2021) - Sharma, Vaibhav; Srinivasan, Alagiri; Nikolajeff, Fredrik; Kumar, Saroj
Abstract: Biomineralization can be considered as nature's strategy to produce and sustain biominerals, primarily via creation of hard tissues for protection and support. This review examines the biomineralization process within the hard tissues of the human body with special emphasis on the mechanisms and principles of bone and teeth mineralization. We describe the detailed role of proteins and inorganic ions in mediating the mineralization process. Furthermore, we highlight the various available models for studying bone physiology and mineralization starting from the historical static cell line-based methods to the most advanced 3D culture systems, elucidating the pros and cons of each one of these methods. With respect to the mineralization process in teeth, enamel and dentin mineralization is discussed in detail. The key role of intrinsically disordered proteins in modulating the process of mineralization in enamel and dentine is given attention. Finally, nanotechnological interventions in the area of bone and teeth mineralization, diseases and tissue regeneration is also discussed. Statement of Significance: This article provides an overview of the biomineralization process within hard tissues of the human body, which encompasses the detailed mechanism innvolved in the formation of structures like teeth and bone. Moreover, we have discussed various available models used for studying biomineralization and also explored the nanotechnological applications in the field of bone regeneration and dentistry. Graphical abstract: Image, graphical abstract